Discourse Tradition and Religious Education: Islamic Educational Values In The Perang Timbung Cultural Practice - Padli, Erwin; Bin Haji Othman , Mohamad Khairi; Hajimia, Hafizah; Ahmad Sanusi; Ahmad Aprillah (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The spread of Western culture and technological advancement has led to a moral and character crisis in society, impacting social and cultural life. Collaborative efforts among families, schools, and communities are necessary to counteract these negative influences. One potential approach is preserving traditions containing positive values, such as the Perang Timbung tradition in Pejanggik Village. This qualitative study with descriptive-analytic methods aimed to examine Islamic educational values in the Perang Timbung tradition and its relevance in strengthening community character. Data sources included community members, including community leaders, religious figures, and the Perang Timbung tradition organizers, as well as library resources comprising books and scientific literature. Data collection was conducted through observation, interviews, and documentation, with data analysis involving reduction, presentation, and conclusion drawing. Research findings revealed that the Perang Timbung tradition contains Islamic educational values, specifically worship values, gratitude values, mutual cooperation values, and deliberation values. These values play a crucial role in forming positive character and strengthening community faith and solidarity.